2018
DOI: 10.18632/oncotarget.25134
|View full text |Cite
|
Sign up to set email alerts
|

An improved method for culturing patient-derived colorectal cancer spheroids

Abstract: Recent advances allowed culturing and examination of patient-derived colorectal cancer (PD-CRC) cells as organoids or spheroids. To be applied to practical personalized medicine, however, current methods still need to be strengthened for higher efficiency. Here we report an improved method to propagate PD-CRC tumor initiating cells (TICs) in spheroid culture. We established > 100 cancer spheroid lines derived from independent colorectal cancer patients employing a serum-containing medium with additional inhibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 34 publications
(54 citation statements)
references
References 38 publications
(49 reference statements)
1
51
1
1
Order By: Relevance
“…Our success rate in growing spheroids from primary tissue was at 88%, which is signi cantly higher than previously reported for work on patient-derived 3D models (e.g. Miyoshi et al reported a success rate of 73% in patient-derived colorectal spheroids (Miyoshi et al, 2018). Spheroids which failed to grow (4 out of 31) were mostly due to contamination with bacteria or fungi (in 3 cases), or low quality of the original tissue piece which resulted in a low yield of viable epithelial cells after single cell extraction (in 1 case).…”
Section: Discussioncontrasting
confidence: 59%
“…Our success rate in growing spheroids from primary tissue was at 88%, which is signi cantly higher than previously reported for work on patient-derived 3D models (e.g. Miyoshi et al reported a success rate of 73% in patient-derived colorectal spheroids (Miyoshi et al, 2018). Spheroids which failed to grow (4 out of 31) were mostly due to contamination with bacteria or fungi (in 3 cases), or low quality of the original tissue piece which resulted in a low yield of viable epithelial cells after single cell extraction (in 1 case).…”
Section: Discussioncontrasting
confidence: 59%
“…Recently, we established hCRC organoid/spheroid lines and patientderived tumor xenografts by an improved method (32,33). We examined 57 cases of hCRCs in which organoids or patient-derived tumor xenografts were successfully established.…”
Section: Il17rb Marks Mouse Intestinal Tscs In An Il-13-dependent Manmentioning
confidence: 99%
“…Primary CRC specimens were obtained from patients who underwent colorectal resection and small pieces of tissue were transplanted into the subcutaneous tissues of immunodeficient female nude mouse (KSN/Slc mouse, SLC, Shizuoka, Japan) to establish PDXs. Spheroids were cultured as previously described [45]. These experiments were approved by the institutional Animal Ethics and Research Committee, Kyoto University (MedKyo 18148).…”
Section: Patient-derived Tumor Xenografts (Pdx) and Patient-derived Cmentioning
confidence: 99%